ITRAX data from dead mangrove trees in the Gulf of Carpentaria, Australia, mid intertidal site T2-3 - James Z Sippo (PANGAEA, 2021)
A massive mangrove dieback event occurred in 2015/2016 along ~1000 km of pristine coastline in the Gulf of Carpentaria, Australia. Elemental analysis of wood cross sections of Avicennia marina revealed 30-90 fold increase in Fe concentrations in dead mangroves just prior to their mortality. This ITRAX data contains multiple elements with radiocarbon dates from the beginning of the trees life to the time of mortality from site T2-3 in the mid intertidal zone.